Distinct roles of programmed death ligand 1 alternative splicing isoforms in colorectal cancer. Issue 1 (9th November 2020) - Wang, Chaoyan; Weng, Menghan; Xia, Shuli; Zhang, Min; Chen, Chaoyi; Tang, Jinlong; Huang, Dan; Yu, Hongfei; Sun, Wenjie; Zhang, Honghe; Lai, Maode
Abstract: Although anti–programmed death‐1 (PD‐1)/programmed death ligand 1 (PD‐L1) immunotherapy has achieved great success in some cancers, most colorectal cancer (CRC) patients remain unresponsive. Therefore, further clarification of the underlying mechanisms is needed to improve the therapy. In this study, we explored the distinct functions of different PD‐L1 alternative splicing isoforms in CRC. We investigated the biological functions in PD‐L1 knocked down/knockout cells, which were verified through overexpression of PD‐L1 isoforms a, b, and c. The roles of PD‐L1 isoforms in immune surveillance resistance was also analyzed. Meanwhile, we performed RNA‐seq to screen the downstream molecules regulated by PD‐L1 isoforms. Finally, we detected PD‐L1 and PD‐L1 isoforms levels in a cohort of serum samples, two cohorts of CRC tissue samples, and analyzed the correlation of PD‐L1 isoforms with PD‐1 blockade therapy response in two clinical CRC cases. The results indicated that PD‐L1 knockout inhibited proliferation, migration, and invasion, and isoform b exerted a more significant inhibitory effect on T cells than the other two isoforms. Moreover, isoform c could promote CRC progression through regulating epithelial‐mesenchymal transition. Clinical data showed that CRC patients with positive PD‐L1 expression were associated with poorer overall survival. High serum PD‐L1 level was associated with poor prognosis. The level of isoform b or c was negatively associated with prognosis, and a higher level of isoform b was associated with a good response to anti–PD‐1 therapy. In conclusion, isoform b should be considered as a biomarker for clinical responsiveness to anti–PD‐1/PD‐L1 immunotherapy; isoform c had a prometastatic role and is a new potential target for CRC therapy. Abstract : In this report, we found that PD‐L1 isoform b could exert a more significant inhibitory effect on T cells than the other two isoforms, and it should be considered as a biomarker of clinical response to immune checkpoint blockade therapy. PD‐L1 isoform c is a prometastatic gene that promotes colorectal cancer progression through regulating epithelial‐mesenchymal transition. It should be considered as a potential prognostic biomarker and an effective target for tumor therapy. Moreover, these findings raise the possibility that PD‐L1 alternative splicing might become a novel target for colorectal cancer immunotherapy.